4
$\begingroup$

The problem:

To make things easier on us so we don't have to use an underbrace, I'm going to declare:

$$\Psi(x,n) := \underbrace{x^{x^{x^{x^{\dots}}}}}_n$$

And we evaluate $f$ from the topright to the bottom left (like a calculator does).

Question: What is $$\Psi'(x,n) = \frac{\partial}{\partial x}\Psi(x,n) = \text{?}$$

My attempt:

Since we know that

$$\begin{align}\frac{\partial}{\partial x}f(x)^x &= \frac{\partial}{\partial x} e^{x \ln f(x)} = \\ &= e^{x \ln f(x)} \left(\frac{x f'(x)}{f(x)} + \ln f(x)\right) = \\ &= f(x)^x \left(\frac{x f'(x)}{f(x)} + \ln f(x)\right),\end{align}$$

We can substitute

$$f(x) := \Psi(x,n-1).$$

So we get

$$\begin{align} \frac{\partial}{\partial x}\Psi(x,n) &= \frac{\partial}{\partial x}\Psi(x,n-1)^x = \\ &= \Psi(x,n-1)^x \left(\frac{x \cdot \frac{\partial}{\partial x} \Psi(x,n-1)}{\Psi(x,n)} + \ln \Psi(x,n-1)\right) = \\ &= \Psi(x,n) \left(\frac{x \cdot \frac{\partial}{\partial x} \Psi(x,n-1)}{\Psi(x,n)} + \ln\underbrace{x^{x^{x^{x^{\dots}}}}}_{n-1}\right) = \\ &= x \cdot \frac{\partial}{\partial x} \Psi(x,n-1) + \Psi(x,n)x^{n-2}\ln x .\end{align}$$

We were able to reduce $n$ by one and get the derivative for $\Psi(x,n)$ in terms of $\Psi(x,n-1)$. If we keep repeating this for $n-1,n-2,\dots,2,1$, we should get the full derivative. However, this is what I'm not quite sure of:

$$\begin{align} \frac{\partial}{\partial x}\Psi(x,n) &= x \cdot \frac{\partial}{\partial x} \Psi(x,n-1) + \Psi(x,n)x^{n-2}\ln x = \\ &= x \cdot \frac{\partial}{\partial x} \Psi(x,n-2) + x \cdot \Psi(x,n-1)x^{n-3}\ln x + \Psi(x,n)x^{n-2}\ln x = \dots \\ \dots &= x \cdot \frac{\partial}{\partial x} \Psi(x,1) + \Psi(x,2)x^{n-2}\ln x + \dots + \Psi(x,n)x^{n-2}\ln x = \\ &= x + \ln x \cdot x^{n-2} \cdot \sum_{k=2}^n \Psi(x,k) = x + \ln \Psi(x,n-1) \sum_{k=2}^n \Psi(x,k) \end{align}$$

So rewriting it with the underbrace notation we get: $$\frac{\partial}{\partial x} \underbrace{x^{x^{x^{x^{\dots}}}}}_n = x + \ln \underbrace{x^{x^{x^{x^{\dots}}}}}_{n-1} \sum_{k=2}^n \underbrace{x^{x^{x^{x^{\dots}}}}}_k$$

Questions:

$1$. Is this correct? Are my calculations right?

$2$. Is there a better way to write the final answer?

$3$. Is there a name for this $(\Psi)$ function?

$4$. Can we generalize $\Psi(x,n)$ for rational (and perhaps irrational) $n$'s?

$5$. What could be the derivative of $\Psi(x,n)$ for such rational / irrational $n$'s?

$\endgroup$
  • 1
    $\begingroup$ I would suggest looking into tetration. $\endgroup$ – Peter Foreman Apr 12 at 18:23
  • $\begingroup$ @PeterForeman Thank you! I was searching all over the internet but Google didn't like my search term of "x^x^x..." .I guess you just really need to know the name of things to be able to find them :) $\endgroup$ – Daniel P Apr 12 at 18:25
  • $\begingroup$ I don't think it is correct. $\endgroup$ – Thomas Andrews Apr 12 at 18:58
  • $\begingroup$ The problem is that if $\Psi(x,n)$ is evaluated from the top right to left, your recursion is $$\Psi(x,n)=x^{\Psi(x,n-1)}$$ and not $$\Psi(x,n)=(\Psi(x,n-1))^x.$$ With your recursion, $\Psi(x,n)=x^{x^{n-1}},$ which is much easier to take the derivative of. But this is the left-to-right interpretation. $\endgroup$ – Thomas Andrews Apr 12 at 19:01
5
$\begingroup$

I think your answer is incorrect. Your recursion $$\Psi(x,n)=\left(\Psi(x,n-1)\right)^x$$ defines the left-to-right interpretation of your expression. The value of the left-to-right interpretation yields a simple $\Psi(x,n)=x^{(x^{n-1})}.$ The derivative in this left-to-right case is $$\frac{\partial}{\partial x}\Psi(x,n)=\Psi(x,n)\left(\frac{1}{x}x^{n-1}+(n-1)x^{n-2}\log x \right)=\Psi(x,n)x^{n-2}\left(1+(n-1)\log x\right)$$

But your question asked for a right-to-left reading, which yields the recursion: $$\Psi(x,n)=x^{\Psi(x,n-1)}$$

The derivative here is going to be messier.

Write it as $\Psi_n(x)$ for slight ease. Then, for $n=0,$ $\Psi_0(x)=1$ and for $n>0,$ $\Psi_n(x)=x^{\Psi_{n-1}(x)}=e^{\log(x)\Psi_{n-1}(x)}$. Then we apply the chain rule: $$\Psi_n'(x)=\left(\frac{1}{x}\Psi_{n-1}(x)+\log(x)\Psi_{n-1}'(x))\right)\Psi_n(x)$$

If we then write this in terms of $$\Phi_n(x)=\frac{\Psi_n'(x)}{\Psi_n(x)}$$ (which we can see as the derivative of $\log\Psi_n(x).$) Then $\Phi_0(x)=0$ and when $n>0$:

$$\Phi_n(x)=\Psi_{n-1}(x)\left(\frac{1}{x}+\log(x)\Phi_{n-1}(x)\right)$$

This is going to get ugly, but:

$$\begin{align}\Phi_n(x)&=\Psi_{n-1}(x)\left(\frac{1}{x}+\log(x)\Psi_{n-2}(x)\left(\frac{1}{x}+\Psi_{n-3}(x)\log(x)\left(\frac{1}{x}+\cdots\right)\right)\right)\\ &=\frac{1}{x}\sum_{k=1}^{n}\left(\log^{k-1}(x)\Psi_{n-1}(x)\Psi_{n-2}(x)\cdots \Psi_{n-k}(x)\right) \end{align}$$

Then $$\Psi_n'(x)=\Psi_n(x)\Phi_n(x)=\frac{1}{x}\sum_{k=1}^{n}\left(\log^{k-1}(x)\Psi_n(x)\Psi_{n-1}(x)\Psi_{n-2}(x)\cdots \Psi_{n-k}(x)\right)$$

For example, $$\begin{align}\Psi_2'(x)&=\frac{1}{x}\Psi_2(x)\Psi_1(x)\left(1+ \log(x)\Psi_0(x)\right)\\ &=\frac1x \cdot x^x\cdot x(1+\log(x)) \\&=x^x \left(1+\log(x)\right) \end{align}$$

and $$\begin{align}\Psi_3'(x) &= \frac{1}{x}\Psi_3(x)\Psi_2(x)\left(1+\log(x)\Psi_1(x)+\log^2(x)\Psi_1(x)\Psi_0(x)\right)\\ &=\frac{1}{x}\cdot x^{x^x}\cdot x^x\left(1+x\log(x)+x\log^2(x)\right) \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.